EMPIRICAL ANALYSIS OF CASH POLICY OF UK FIRMS PRE AND POST FINANCIAL CRISES - SHAKEEL, MAHNOOR (2019)
The analysis of corporate cash policy of UK firms reveals an increasing trend before the crises which is coupled with the decreasing investments, but crises results in a structural change in the corporate liquidity management behavior of firms, which is a consequence of change in the characteristics of firms. The change in the corporate cash policy persists for the pre-existing firms regardless of whether the firms are financially constraint or not. The change in the corporate cash policy after the crises for the pre-existing firms can be explained by the changes in the characteristics of firms before crises and this phenomenon prevailed irrespective of their size and their dividend paying characteristic. In order to derive these conclusions this study progresses in steps, where each step uncovers a different aspect of the corporate cash policy of UK firms before and after the crises. For most of the analysis carried out, the pattern of cash holding is associated with investments to infer whether the reason of cash buildup or decline is that firms have reduced their investments or started investing, respectively. This technique is adopted after a negative relation between cash holding and investments is proved. The corporate cash policy of UK firms challenges the precautionary reasons of cash buildup during crises.